Occupational injuries and health-seeking behavior of informal sector waste collection workers in Nellore, India - Sai Divya Chinthapatla; Rajnarayan Ramshankar Tiwari (Wolters Kluwer Medknow Publications, 2024)
Introduction: Waste collection workers are exposed to occupational injuries at every step in the process of waste collection and disposal, from the point of collection at homes, during transportation, and at the sites of recycling or disposal. This study was undertaken to assess the prevalence of injuries among municipal waste collection workers and their health-seeking behavior for the injuries. Methods: This cross-sectional study included 422 workers from randomly selected 20 wards in four zones of Nellore. The information regarding sociodemographic, occupational, and injury characteristics were collected using a pre-tested questionnaire by conducting a face-to-face interview with each of the study participants. Results: Two hundred and four (48.3%) workers suffered from injury in the past 12 months. A shorter duration of the job, a lack of safety training, and a lack of awareness about the risk of injury on the job were significantly associated with the occurrence of injuries. The health-seeking behavior was found to be poor, with only 40.7% of those who suffered injury and 30.6% of overall workers preferring to approach any health-care facility for the treatment of wounds. Conclusion: The informal sector waste collection workers are at risk of injuries while pursuing their occupation. The health seeking behavior was found to be poor among them.